Hearing healthcare gaps in LMICS: snapshot from a semi-urban community in Nigeria (2021)
Background: Low and middle-income countries (LMICs) have high prevalence of hearing loss which are mainly due to preventable causes. While urban communities in LMICs are likely to have functional hearing healthcare delivery infrastructure, rural and semi-urban communities may have different reality. Objectives: This study aimed to provide: (i) a snapshot of the burden of ear diseases and (ii) a description of available hearing healthcare resources in a semi-urban Nigerian community. Methods: A cross-sectional study of households selected by multistage random sampling technique. Seventy-four participants: 39 males and 35 females with mean age of 34 years ± 5.24 were recruited and answered a structured questionnaire. In addition, the availability of hearing healthcare services in 15 health centers within the community were determined. Results: All participants reported recent occurrence of ear complaints or gave similar history in a household member. Common complaints were ear discharge, ear pain and hearing loss. Medical intervention was sought from patent medicine stores, hospitals and traditional healers. None of the assessed hospitals within the study site was manned by an ENT surgeon or ENT trained nurse. Conclusion: Despite the heavy burden of ear complaints there is inadequate hearing healthcare delivery in a typical LMIC community. This highlights the need for urgent improvement of hearing healthcare